Membangun Pemahaman Siswa Sekolah Vokasi tentang Konsep dan Implementasi Internet of Things - Sondakh, Debby Erce; Pungus, Stenly Richard (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2024)
The Internet of Things (IoT) has been a revolutionary change in information and communication technology, affecting various aspects of daily life. Vocational schools play a key role in preparing students to work in various industries, and an understanding of IoT has become one of the increasingly necessary competencies in today's workforce. On the other hand, the IoT has not been an integrated part of the learning materials at the SMK Negeri 1 Modoinding in North Sulawesi. Therefore, IoT education is carried out through community service program. Students were given materials that included history, understanding basic concepts, components, protocols, applications, advantages, challenges, and the future of IoT. To evaluate the impact of the program, a pengukuran awal and pengukuran akhir were conducted. The results of the data analysis showed that the pengukuran akhir points were consistently higher than the pengukuran awal points in all material items, indicating a significant increase in student understanding after the program. This improvement reflects that this activity was successful in building students' understanding of IoT and providing better insight into the potential of this technology in supporting the vocational sector. It is hoped that the understanding gained by the students in this activity will provide a strong foundation for them to face the development of IoT technology in the future.